2022
DOI: 10.1038/s41598-022-22163-7
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral therapy resistance mutations among HIV infected people in Kazakhstan

Abstract: In Kazakhstan, the number of people living with HIV (PLHIV) has increased steadily by 39% since 2010. Development of antiretroviral therapy (ART) resistance mutations (ARTRM) is a major hurdle in achieving effective treatment and prevention against HIV. Using HIV pol sequences from 602 PLHIV from Kazakhstan, we analyzed ARTRMs for their association with factors that may promote development of ARTRMs. 56% PLHIV were infected with HIV subtype A6 and 42% with CRF02_AG. The ARTRM Q174K was associated with increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Another study of 165 ART-naïve patients, with sequences collected between 2009 and 2013, reported a low (3%) prevalence of drug resistance [ 13 ]. A study of 602 sequences collected between 2017 and 2019 from ART-experienced patients reported high-level NRTI resistance in 10% of sequences and high-level NNRTI resistance in 21% of them [ 7 ]. Comparing these earlier prevalence estimates to our findings of 16.8% and 30% high-level NRTI and NNRTI resistance, respectively, our current study suggests an increase in the prevalence of drug resistance in Kazakhstan over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study of 165 ART-naïve patients, with sequences collected between 2009 and 2013, reported a low (3%) prevalence of drug resistance [ 13 ]. A study of 602 sequences collected between 2017 and 2019 from ART-experienced patients reported high-level NRTI resistance in 10% of sequences and high-level NNRTI resistance in 21% of them [ 7 ]. Comparing these earlier prevalence estimates to our findings of 16.8% and 30% high-level NRTI and NNRTI resistance, respectively, our current study suggests an increase in the prevalence of drug resistance in Kazakhstan over time.…”
Section: Discussionmentioning
confidence: 99%
“…World Health Organization (WHO) guidelines in 2021 recommended 3TC/FTC + TDF + DTG (lamivudine–emtricitabine + tenofovir + dolutegravir) as the preferred first-line regimen for adults and adolescents and 3TC + TDF + EFV (3TC + TDF + efavirenz) as the preferred alternative first-line regimen [ 4 ]. In Kazakhstan, current ART guidelines follow the WHO recommendations, though there have been guideline changes in recent years ( Table 1 ) [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection pressure predicted using the FUBAR method performed separately for each group indicated four distinct DRM sites under positive selection pressure, including DRM site 138 in the ART-naïve group, DRM site 188 in the ART-experienced group, and DRM sites 103 and 115 in the unknown status group, while all other DRM sites were under negative selection. Further analysis of DRM sites between the 3 groups showed DRM sites 69, 101, 179, 184, and 190 (−0.99, −0.95, −0.97, −0.93, and −0.99, respectively) to be under high negative selection pressure in the ART-naïve group; DRM sites 10, 30,41,54,65,100,101,190,221, and 230 (−1.00, −1.00, −0.94, −0.99, −0.97, −0.99, −0.87, −0.99, −0.95, and −0.93, respectively) to be under high negative selection pressure in the ART-experienced group; while DRM sites 46, 47, 54, 106, and 138 (−0.95, −0.90, −0.99, −0.99, and −0.98, respectively) to be under high negative selection pressure in the unknown status group. Moreover, DRM site 103 was observed under positive selection in the ART-experienced group (Supplementary Table S1).…”
Section: Genomic Variability and Selection Pressure On Drm Sitesmentioning
confidence: 98%
“…This plays an important role in ensuring treatment adherence and selecting the most effective combinations of antiretroviral drugs to minimize resistance. For various reasons some patients demonstrate high viral loads even when taking antiretroviral drugs due to development of HIV drug resistance [9][10][11]. Therefore, the development of methods for the prediction of HIV drug resistance is of high importance.…”
Section: Introductionmentioning
confidence: 99%